LA NECESIDAD DE REFORMAR EL ARTÍCULO 338 DEL CÓDIGO TRIBUTARIO, ELIMINANDO LA PRESCRIPCIÓN COMO MODO DE EXTINGUIR LAS ACCIONES Y LAS PENAS POR INFRACCIONES TRIBUTARIAS - Puchaicela, Ximena Alexandra (2016)
This thesis entitled: "THE NEED TO REFORM THE ART. TAX CODE 338, ELIMINATING THE REQUIREMENT AS SHARES WAY TO EXTINGUISH AND PENALTIES FOR TAX VIOLATIONS”, it made based on the general rules for graduation, and prior to obtaining a bachelor's degree in Jurisprudence and Lawyer, with in order to prevent further causing economic damage to the state, because the limitation of actions and pecuniary penalties, the tax authorities raised against taxpayers, to pass away the time set by tax rules to comply with tax obligations The non-collection of these taxes generate large economic losses to the country and the consequent reduction of resources for meeting the basic needs of the population. The theoretical, legal and doctrinal gathering, conducting surveys and interviews allowed me to get recognized criteria very clear and precise basis of literature, which contributed to the verification of the objectives and the recruitment of the hypothesis; both the Constitution of the Republic of Ecuador, as the Tax Code, which determine explicit rules on the question asked, thus achieving the approach of conclusions and recommendations, in order to establish my law reform proposal.